2012
DOI: 10.1007/s10661-012-2778-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal analysis of ground level ozone and nitrogen dioxide concentration across the twin cities of Pakistan

Abstract: The analyses presented in this paper include the concentration levels of NO2 and O3 measured during 2 successive years in twin cities (Rawalpindi and Islamabad) of Pakistan from November 2009 to March 2011. NO2 was determined using the passive sampling method, while ozone was determined by Model 400E ozone analyzer. The average NO2 and O3 concentration in twin cities of Pakistan was found to be 44 ± 6 and 18.2 ± 1.24 ppb, respectively. Results indicate that the concentration of NO2 and O3 show seasonal variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Correlations between NO 2 and meteorological variables have been investigated quantitatively at individual ground‐based locations [ Delaney and Dowding , ; Noble et al ., ; Roberts‐Semple et al ., ; Song et al ., ], at multiple ground‐based sites within urban areas [ Ahmad et al ., ; Ahmad and Aziz , ; Hatzianastassiou et al ., ], and qualitatively described as part of discussion of seasonal trends [e.g., Prasad et al ., ; Wei et al ., ]. These relationships are summarized in Figure and discussed below for each meteorological variable examined.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Correlations between NO 2 and meteorological variables have been investigated quantitatively at individual ground‐based locations [ Delaney and Dowding , ; Noble et al ., ; Roberts‐Semple et al ., ; Song et al ., ], at multiple ground‐based sites within urban areas [ Ahmad et al ., ; Ahmad and Aziz , ; Hatzianastassiou et al ., ], and qualitatively described as part of discussion of seasonal trends [e.g., Prasad et al ., ; Wei et al ., ]. These relationships are summarized in Figure and discussed below for each meteorological variable examined.…”
Section: Introductionmentioning
confidence: 99%
“…When OH is converted to the peroxy radical (HO 2 ) in the presence of ozone or VOCs, production of NO 2 from NO can be enhanced, but OH can also negatively impact NO 2 concentrations via reactions that form nitric acid [ Jacob , ]. A number of studies have found NO 2 concentrations positively correlated with RH [e.g., Ahmad et al ., ; Ahmad and Aziz , ; Noble et al ., ; Reddy et al ., ; Roberts‐Semple et al ., ; Song et al ., ]. Correlations between NO 2 and RH can be complicated by precipitation and by temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the increase of motor vehicles in traffic in the study area, dense population and building blocks located in the center and southern parts of the study area, meteorological and topographical factors (Briggs et al, 2008, Mayer, 1999, Ahmad and Aziz, 2013, Lee et al, 2013, Lin et al, 2013, Zbieranowski and Aherne, 2012, Evci, 2009, Yang et al, 2005, the level of nitrogen dioxide (NO2) concentrations are higher in these points. …”
Section: Resultsmentioning
confidence: 99%
“…Briggs et al (2008), Mayer (1999), Ahmad and Aziz (2013) focus on nitrogen dioxide (NO2) that is a secondary pollutant and derived from especially motor vehicles. Brauer et al (2003) and Nerriere et al (2005) focus on particulate matter (PM10 and PM2.5) as an urban air pollutant causes a decrease in the level of air quality, while the level of individual exposure to pollution increases in urban areas.…”
Section: Literature Reviewmentioning
confidence: 99%